Synthesis and characterisation of glass ionomer cement from soda lime silica waste glass or Anadara granosa L. shell - Thoo, Francis Voon Wai (2014)
Glass ionomer cements (GIC) are produced via acid-base reaction between calcium-fluoroaluminosilicate glass powders and freeze-dried polyacrylic acid (PAA) powder. Soda lime silica (SLS) waste glass, mainly consist of silica dioxide (SiO2) and Anadara granosa (cockle shells), mainly consist of calcium carbonate (CaCO3), have been utilised in this study as the prime source of SiO2 and CaCO3 by incorporating it as part of glass components for production of GIC. Therefore, the main objectives of this research were to study the potential of SLS waste glass and Anadara granosa shells as raw materials for synthesis of GIC and investigate the effect of the waste materials towards setting reaction and compressive strength of GIC. GIC were produced by introducing distilled water into the pre-mixed glass and PAA powders in a powder: liquid weight ratio of 4:1. Energy dispersive X-ray spectrometry (EDX), Thermogravimetric Analysis (TGA), X-Ray Diffraction (XRD), Solid State Nuclear Magnetic Resonance (SS NMR), Fourier-Transform Infrared spectroscopy (FTIR), and compressive strength evaluation were employed for characterisations of waste materials, glasses and GIC. Result from EDX showed that SLS waste glass contained more than 70% of SiO2 and result from TGA and EDX showed that the percentage of CaCO3 in Anadara granosa was more than 98 %. This suggested that both SLS waste glass and Anadara granosa shell were ideal natural sources of SiO2 and CaCO3 and suitable to be utilised in GIC production. Both FTIR and XRD analyses implied that calcite was the only polymorph found in Anadara granosa shell. The absence of sharp diffraction peaks in XRD pattern suggested that all glass types produced namely GWX 1 (using high purity raw material), GWX 2 (using SLS waste glass as source of SiO2), and GWX 3 (using Anadara granosa as source of CaCO3), were completely amorphous. From SS NMR results, the chemical shift of 29Si suggested that all glasses have Q3 (4Al) structure. When Na content is higher, the chemical shift of 31P chemical shift shifted to a more positive value. The chemical shift of 27Al shifted to a more positive value when Al:P ratio has increase. FTIR result showed that setting reaction of all glass types involved the occurrence of cross-linking between polyacrylate chain and metal ions from glass given by gradual conversion of COOH absorption band at 1690-1700 cm-1 into COO-Mn+ absorption band at 1550-1600 cm-1 and hardening of GICs given by gradual conversion of Si-O-H absorption band at 950-969 cm-1 into Si-O-Si absorption band at 1040-1056 cm-1. GIC 2 cements exhibited slower setting rate at initial stage but completely established cross-linking at 1 day ageing whereas GIC 3 cements showed cross-linking completely at 1 hour ageing time which were similar as GIC 1 cement. All cements maintained their compressive strengths throughout the ageing time. At 1 day ageing time, GIC 2 and GIC 3 cements exhibited lower compressive strength of 59.15 MPa and 62.70 MPa, respectively in relative to 69.39 MPa for GIC 1 cements. However, GIC 2 and GIC 3 cements showed increment in compressive strength and achieved slightly higher values than GIC 1 after 7 days and 28 days of ageing time. Sodium content in both GIC 2 and GIC 3 was found to be dominant factor of slow setting rate and low compressive strength at initial stage. Based on analyses conducted in this study, both SLS waste glass and Anadara granosa can be potentially utilised for glass synthesis in GIC production as GIC 2 and GIC 3 cement exhibited similar setting reaction and compressive strength as GIC 1 cement.